Region in the unsolved rearrangement of the national territory (2007)
The difficulties around the application of the concept of “regional” in Colombia are the subject of this text. It approaches to two synchronic and complementary points of view. At the first one, the regional shows up as a product, and it is submitted to external dynamic, framed in what is labeled as globalization. In the second one, the concept of regional appears as an internal dynamic, that looks forward to reduce social-economical unfairness in Colombia, as well as the consolidation of an National State.